2022
DOI: 10.3389/fphar.2022.906073
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuate Myocardial Injury by Inhibiting Ferroptosis Via Inducing KAT5/GPX4 in Myocardial Infarction

Abstract: Myocardial infarction (MI) is a coronary artery-related disease and ranks as the leading cause of sudden death globally. Resveratrol (Res) is a bioactive component and has presented antioxidant, anti-inflammatory and anti-microbial properties. However, the effect of Res on ferroptosis during MI progression remains elusive. Here, we aimed to explore the function of Res in the regulation of ferroptosis and myocardial injury in MI. We observed that the treatment of Res attenuated the MI-related myocardium injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In 2009, Elif Tatlidede et al demonstrated that RSV treatment notably raised cardiac GSH contents and suppressed oxidant responses in DOX-processed rats; Simultaneously, it ameliorated DOX-induced deterioration of cardiac function and myocardial injury [192]. In the following decade, many researchers verified in various models of myocardial injury that RSV can exert an antioxidant effect and protect the myocardium by increasing the level of GSH and upregulating the activity of GSH-dependent antioxidant enzymes [193][194][195][196][197]. Moreover, they revealed that the mechanism by which RSV enhances the GSH system involves the AMPK signaling pathway, the Nrf2 signaling pathway, the Sirt1 pathway, noncoding RNA (miR-149) and the KAT5 gene [193][194][195][196][197].…”
Section: Glutathione System Activatormentioning
confidence: 99%
See 2 more Smart Citations
“…In 2009, Elif Tatlidede et al demonstrated that RSV treatment notably raised cardiac GSH contents and suppressed oxidant responses in DOX-processed rats; Simultaneously, it ameliorated DOX-induced deterioration of cardiac function and myocardial injury [192]. In the following decade, many researchers verified in various models of myocardial injury that RSV can exert an antioxidant effect and protect the myocardium by increasing the level of GSH and upregulating the activity of GSH-dependent antioxidant enzymes [193][194][195][196][197]. Moreover, they revealed that the mechanism by which RSV enhances the GSH system involves the AMPK signaling pathway, the Nrf2 signaling pathway, the Sirt1 pathway, noncoding RNA (miR-149) and the KAT5 gene [193][194][195][196][197].…”
Section: Glutathione System Activatormentioning
confidence: 99%
“…In the following decade, many researchers verified in various models of myocardial injury that RSV can exert an antioxidant effect and protect the myocardium by increasing the level of GSH and upregulating the activity of GSH-dependent antioxidant enzymes [193][194][195][196][197]. Moreover, they revealed that the mechanism by which RSV enhances the GSH system involves the AMPK signaling pathway, the Nrf2 signaling pathway, the Sirt1 pathway, noncoding RNA (miR-149) and the KAT5 gene [193][194][195][196][197]. In addition, RSV can suppress the occurrence of ferroptosis in the myocardium by increasing SLC7A11/GSH and GPX4 [193,195].…”
Section: Glutathione System Activatormentioning
confidence: 99%
See 1 more Smart Citation
“…However, under certain pathological conditions, the transport capacity of SLC7A11 and the activity of GPX4 decreased, finally inducing ferroptosis. 27 SLC7A11 is expressed in various tissues and downregulated in pathological conditions. Similarly to our results, Li et al 28 recently reported that GPX4 expression decreased in ADR-induced myocardial injury in mice, suggesting that upstream SLC7A11 may participate in the ferroptosis of ADR-induced myocardial injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, we found that suffruticosol C has a better inhibitory effect on cell viability than resveratrol at the same concentration. A large number of studies suggested that resveratrol plays a crucial role in autophagy, cell cycle, ferroptosis, and apoptosis [ 24 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. However, in our study, we found that suffruticosol C, unlike resveratrol, only has a specific regulatory effect on autophagy and the cell cycle, but it has no effect on apoptosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%